Pelatihan Mengukir Menggunakan Konsep Matematika Untuk Anak-Anak Di Kelurahan Sandabilik, Kecamatan Makale Selatan - Delastri, Lusiana; Angela, Angela (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2024)
A typical Toraja carving called Pa'sura' is one of the manifestations of Toraja culture. Toraja residents need to recognize the carving motif and understand the meaning behind it. Over time, Toraja carvings are not only used as decorations for tongkonan, alang, and ritual tools, but can be used as decorations such as key chains, cloth motifs, and so on. However, there are still many children in the Sandabilik Village who are less interested in carving because the Toraja carving motifs are very complicated. The motifs in Toraja carvings have geometric patterns. There are several geometric concepts that exist in carving motifs, including points, circles, triangles, squares, rectangles, diamonds, trapezoids, parallelograms, and kites, symmetry, translation, rotation, dilation, and reflection. The objectives of this PKM activity are (1) to introduce Toraja culture, especially carvings and their meanings to children in Sandabilik Village; (2) introduce the geometric concepts contained in the Toraja carving motifs; and (3) providing assistance on how to carve by utilizing mathematical concepts. The stages carried out in the service are socializing about Toraja culture including the introduction of carvings and their meanings, identifying mathematical concepts on motifs, reviewing the identified mathematical concepts, and carving using mathematical concepts. This activity can make children able to carve by utilizing the dominant geometric concept in carving motifs. Carving using mathematical concepts can make: (1) children are able to apply their mathematical knowledge to culture; (2) children will better understand and experience cultural activities from a mathematical point of view, thus enabling them to make connections between school mathematics and the real world. Carving activities for children can also develop children's visuospatial reasoning. Visuospatial reasoning can make children more creative in solving everyday problems.